Coral Reef Conditions of Hogow and Dakokayu Islands Southeast Minahasa Regency - Billy N. Ompi; Unstain N.W.J. Rembet; Ari B. Rondonuwu (Sam Ratulangi University, 2019)
This research objective was to determine the condition of Coral Reef ecosystems in Dakokayu and Hogow Islands, Southeast Minahasa Regency. The method that has been used in this studies that is Line Intercept Transect (LIT) by diving activities at 5 meter and 10 meters depth with 50 meters transect length. Each biota passed by the line transect recorded according based on shape of growth.Coral Reefs conditon in Hogow Island in 5 meters and 10 meters depth were categorized as a â€œGoodâ€ where the percentage of live coral cover in 5 meters depth is 70.12% and in 10 meters depthÂ is 55.78%. The condition of Coral Reefs on Dokokayu Island at a depth of 5 meters is categorized â€œGoodâ€ with the percentage of live coral cover is 56.32% while in the 10 meters depth it is categorized as â€œMediumâ€ with the percentage of live coral cover is 48.10%. Water quality parameters such as temperature, salinity, brightness, pH, and dissolved oxygen (DO) are within the range of tolerance for Coral Reefs to survive.Keywords: Condition, Coral Reef, Hogow, DokokayuABSTRAKTujuan penelitian untuk mengetahui kondisi ekosistem terumbu karang di Pulau Dakokayu dan Pulau Hogow, Kabupaten Minahasa Tenggara.Â Metode yang telah digunakan dalam penelitian ini yaitu Line Intercept Transek (LIT) dengan melakukan penyelaman pada kedalaman 5 dan 10 meter dengan panjang transek 50 meter.Â Setiap biota yang dilewati transek akan dicatat menurut bentuk pertumbuhannya. Secara umum, kondisi terumbu karang di Pulau Hogow pada kedalaman 5 meter dan 10 meter, dikategorikan Baik dimana persentasi tutupan karang hidup pada kedalaman 5 meter sebesar 70,12% dan pada kedalaman 10 meter sebesar 55,78%.Â Kondisi terumbu karang di Pulau Dokokayu pada kedalaman 5 meter dikategorikan BaikÂ dengan persentase tutupan karang hidup 56,32% sedangkan di kedalaman 10 meter dikategorikanÂ SedangÂ dengan persentase tutupan karang hidup 48,10 %. Parameter kualitas perairan seperti suhu, salinitas, kecerahan, pH, dan oksigen terlarut (DO) berada dalam kisaran toleransi bagi terumbu karang untuk dapat bertahan hidup.Kata Kunci : Kondisi, Terumbu Karang, Hogow, Dokokayu